2003
DOI: 10.1200/jco.2003.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Potential Indicators of the Quality of End-of-Life Cancer Care From Administrative Data

Abstract: Several promising claims-based quality indicators were identified that, if found to be valid and reliable within data systems, could be useful in identifying health-care systems in need of improving end-of-life services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
758
2
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 772 publications
(779 citation statements)
references
References 22 publications
8
758
2
11
Order By: Relevance
“…Policy implications some of the outcomes described in this study have been suggested as valid indicators for evaluating the quality of end-of-life care (Earle et al 2003(Earle et al , 2004(Earle et al , 2005. using administrative data in this way is consistent with a previously published quality framework for palliative and end-of-life care (stewart et al 1999).…”
Section: Other Findings From the Literaturesupporting
confidence: 86%
“…Policy implications some of the outcomes described in this study have been suggested as valid indicators for evaluating the quality of end-of-life care (Earle et al 2003(Earle et al , 2004(Earle et al , 2005. using administrative data in this way is consistent with a previously published quality framework for palliative and end-of-life care (stewart et al 1999).…”
Section: Other Findings From the Literaturesupporting
confidence: 86%
“…Validity and reliability-Face validity, 15 of these indicators has been established by the preliminary work of Earle et al, 23 and Teno et al 26 To assess content validity and reliability, we obtained a random sample of the study subjects who received their care at a tertiary cancer treatment facility and its host hospital in each province: the QEII Health Sciences Centre in NS -the sole tertiary care treatment facility in the province, serving a population of 950 thousand; and the Ottawa Hospital in Ontario -the tertiary care treatment facility, serving a population of 1.5 million in Eastern Ontario. Electronic data abstraction forms were developed in MS Access and pilot tested.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Similarly, previously studies have reported that most patients with malignancy prefer to die at home (Bruera et al, 2002;Earle et al, 2003). But this is not the real situation in clinical practice.…”
Section: Introductionmentioning
confidence: 93%